In Vitro Control of Phytophthora infestans and Alternaria solani Using Crude Extracts and Essential Oils from Selected Plants - Lydia G. Mugao; Phyllis W. Muturi; Bernard M. Gichimu; Ezekiel K. Njoroge (International Journal of Agronomy)
Tomato production is constrained by fungal diseases especially the early and late blight caused by Alternaria solani and Phytophthora infestans, respectively. Control of the two diseases is usually by use of synthetic fungicides which have a long residue effect and also contribute to environmental pollution. Innovative use of biocontrols may offer an eco-friendly and more sustainable solution. This study tested the in vitro efficacy of crude extracts and essential oils of ginger, garlic, tick berry, and Mexican marigold in inhibition of radial growth of A. solani and P. infestans. Extraction of the crude extracts was done using distilled water, ethanol, and methanol solvents, while essential oils were extracted using the dry steam distillation method. The extracts and essential oils were used to amend the growth media of the test pathogens before introducing the precultured pathogens. Sterile distilled water and synthetic fungicide, Ridomil Gold®, were used as positive and negative controls, respectively. Fungal growth inhibition was determined by measuring the radial growth of the test pathogens. Both the crude extracts and the essential oils portrayed some efficacy against the test pathogens. Garlic crude extracts were found to be the most effective, while ethanol was the most suitable extraction solvent. Essential oils were more effective in restricting the pathogen growth than crude extracts. Ginger and garlic oil was found to be as effective as the synthetic fungicide, and thus it was concluded that the two plants have strong antifungal properties with high potential of being utilized as biofungicides. However, effective utilization of these products in farmers’ fields may require industrial formulation to improve their efficiency.